Nurses' Compliance Towards Infection Control Practices at Sulu Sanitarium and General Hospital - Sangkula , Sahid (Journal of Interdisciplinary Perspectives, 2024)
This descriptive-correlational study assessed nurses' compliance towards infection control practices at Sulu Sanitarium and General Hospital with a sample size of 100, selected through non-probability sampling using purposive sampling. The study utilized statistical measures such as weighted mean, standard deviation, t-test for independent samples, One-way ANOVA, and Pearson's r. The findings of the study indicate that, on average, nursing personnel demonstrate compliance towards infection control practices. Additionally, variables such as gender, age, educational attainment, length of service, and appointment status were found not to significantly influence compliance towards infection control practices. Furthermore, it was observed that individuals who strongly agreed with the compliance towards infection control practices regarding awareness of knowledge and adherence to protocol were likely the same group who agreed with aspects such as training and communication, attitude and practices, and self-evaluation. These findings support the Health Belief Model (HBM), which suggests that cognitive processes influence nurses' behaviors in the context of infection control. In the framework of HBM, nurses' compliance is analyzed in terms of perceived susceptibility to infections, recognizing the risks faced in healthcare settings, and perceived severity, highlighting the consequences of non-compliance on both personal and patient health.